PERSEPSI PETANI TERHADAP KINERJA PENYULUH DALAM PENGEMBANGAN PADI ORGANIK DI KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - Sari, Juwita; Nurmayasari, Indah; Yanfika, Helvi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aimed to analyze the farmers’ perception level on performance of extension workers in organic paddy development, the factors related to farmers’ perception on the performance, and the difference of perceptions between organic paddy farmers’ and nonorganic paddy farmers’ in performance of extension workers in organic paddy development in Pagelaran Subdistrict, Pringsewu district. This research was conducted in Pagelaran Village and Gemah Ripah Village in Pagelaran subdistrict, Pringsewu District. Respondents were 48 farmers’ consisting of all 24 organic paddy farmers’s and 24 nonorganic paddy farmers’ which taken randomly. Data were analyzed using Rank Spearman and Mann Whitney. Result showed that farmers’ perception on extension workers performance in organic paddy development was included in medium classification. Factors with real related to farmers’ perception toward performance of extension in organic paddy development were their age, knowledge, duration as a farmer and social interactions. There was no difference between organic paddy farmers’perception and nonorganic paddy farmers’ perception toward performance of extension in organic paddy development. Both organic paddy farmers’ and nonorganic paddy farmers’ gave a good enough valuation towards performance of extension in organic paddy development. Key words : extension performance, farmer perception, organic paddy